2016
DOI: 10.1002/hipo.22573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroconvulsive seizures on cognitive flexibility

Abstract: Electroconvulsive seizures (ECS), an animal model of electroconvulsive therapy, strongly stimulate hippocampal neurogenesis, but it is not known how this relates to the therapeutic effect or to the unwanted cognitive side effects. Recent findings suggest that neurogenesis might be important for flexible learning in changing environments. We hypothesize that animals receiving ECS treatment, which induces hippocampal neurogenesis, will show enhanced cognitive flexibility compared with controls. We have utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
(93 reference statements)
0
6
0
1
Order By: Relevance
“…While the mechanism of action of ECT remains incompletely understood, its potent effects on neuroplasticity may underlie its antidepressant effects (10,84), though critical gaps in this literature remain. Electroconvulsive seizures (the analog of ECT in animal models) affect many neuroplastic processes, including gliogenesis, increased axospinous synapses in the CA1 pyramidal layer, increase in number of mushroom spines, axonal sprouting in the dentate gyrus, neurogenesis, as well as regulation of neurotrophic factors (85,86). Cognitive flexibility, operationalized as the ability to flexibly learn new and unlearn old associations as novel situations arise, has been shown to improve following electroconvulsive seizure in rodents (86).…”
Section: D-cycloserinementioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism of action of ECT remains incompletely understood, its potent effects on neuroplasticity may underlie its antidepressant effects (10,84), though critical gaps in this literature remain. Electroconvulsive seizures (the analog of ECT in animal models) affect many neuroplastic processes, including gliogenesis, increased axospinous synapses in the CA1 pyramidal layer, increase in number of mushroom spines, axonal sprouting in the dentate gyrus, neurogenesis, as well as regulation of neurotrophic factors (85,86). Cognitive flexibility, operationalized as the ability to flexibly learn new and unlearn old associations as novel situations arise, has been shown to improve following electroconvulsive seizure in rodents (86).…”
Section: D-cycloserinementioning
confidence: 99%
“…Electroconvulsive seizures (the analog of ECT in animal models) affect many neuroplastic processes, including gliogenesis, increased axospinous synapses in the CA1 pyramidal layer, increase in number of mushroom spines, axonal sprouting in the dentate gyrus, neurogenesis, as well as regulation of neurotrophic factors (85,86). Cognitive flexibility, operationalized as the ability to flexibly learn new and unlearn old associations as novel situations arise, has been shown to improve following electroconvulsive seizure in rodents (86). Studies of ECT in humans have also shown effects on neuroplasticity markers, including changes in hippocampal and amygdala volumes (10,84,87), peripheral brainderived neurotrophic factor (88), and default mode network connectivity (89).…”
Section: D-cycloserinementioning
confidence: 99%
“…We observed no difference in tonic seizure duration over the treatment course, which is in line with other studies (29). Nonetheless, both a slight increase (28) and decrease (30, 31) in ECS seizure duration over administration days have been observed. Our interpretation is that several factors such that age, weight, stimulus parameters used, and rat strain might affect the seizure duration.…”
Section: Discussionmentioning
confidence: 99%
“…Neben dem Krampfanfall und möglicherweise auch der Suppression des Krampfanfalles als essenzielle Wirkmechanismen werden weitere diskutiert. So gibt es eine Reihe von Studien, die verschiedenste neurophysiologische und neurofunktionelle kurz-und langfristige Veränderungen durch EKT festgestellt haben: ➣ kurz-und langfristiger Anstieg neurotropher Faktoren wie BDNF (Brain Derived Nerve Factor; Okamoto et al, 2008;Piccinni et al, 2009;Rocha et al, 2016) und NGF (Nerve Growth Factor; Bilgen et al, 2014) ➣ konsekutiv Neurogenese und Neuroplastizität im Hippocampus und anderen Hirnregionen (Bolwig & Madsen, 2007;Lamont et al, 2005;Madsen, 2000;Michael et al, 2003a;Olesen et al, 2017;Otabe et al, 2014;Schloesser et al, 2015;Smith et al, 2014;Svensson et al, 2016;Tendolkar et al, 2013) ➣ kurzfristig verstärkte Freisetzung von Neurotransmittern: Dopamin , Serotonin (Baldinger et al, 2014;Ishihara & Sasa, 1999), GABA (Sanacora et al, 2003), Noradrenalin (Kelly & Cooper, 1997) ➣ Beeinflussung der Rezeptorenfunktion im Gehirn: 5-HT3 , 5-HT1A , 5-HT2A ¯ (Ishihara & Sasa, 1999) ➣ Freisetzung verschiedenster Hormone wie Prolaktin und TSH (Abrams & Sukartz, 1985;Abrams, 1992;Aperia et al, 1985), Cortisol und ACTH (Fink & Nemeroff, 1989;Florkowski et al, 1996), Endorphine (Abrams, 1992), Oxytocin (Scott et al, 1989;Whalley et al, 1987 (Abbott et al, 2013) ➣ Normalisierung bei depressiven Patient*innen im Vergleich zu psychisch Gesunden verminderter Glutamat/ Glutamin (Glx)-Konzentrationen im linken anterioren Cingulum (ACC) (Pfleiderer et al, 2003)…”
Section: Wirkmechanismen Der Ektunclassified